The Role of NOX4 and TRX2 in Angiogenesis and Their Potential Cross-Talk - Chaofei Chen; Li Li; Huanjiao Jenny Zhou; Wang Min (MDPI AG, 2017)
The nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) family is the major source of reactive oxygen species (ROS) in the vascular system. In this family, NOX4, a constitutive active form of NOXs, plays an important role in angiogenesis. Thioredoxin 2 (TRX2) is a key mitochondrial redox protein that maintains normal protein function and also provides electrons to peroxiredoxin 3 (PRX3) to scavenge H2O2 in mitochondria. Angiogenesis, a process of new blood vessel formation, is involved in a variety of physiological processes and pathological conditions. It seems to be paradoxical for ROS-producing NOX4 and ROS-scavenging TRX2 to have a similar role in promoting angiogenesis. In this review, we will focus on data supporting the role of NOX4 and TRX2 in angiogenesis and their cross-talks and discuss how ROS can positively or negatively regulate angiogenesis, depending on their species, levels and locations. NOX4 and TRX2-mediated ROS signaling could be promising targets for the treatment of angiogenesis-related diseases.